Correlates of Expressed Emotion Among Family Members of Individuals Who Sought Treatment for Opioid Use. Issue 11 (November 2020) - Ellis, Jennifer D.; Resko, Stella M.; Brown, Suzanne; Agius, Elizabeth; Kollin, Rachel; Burlaka, Viktor
Abstract : Abstract: Expressed emotion has been robustly associated with negative mental health outcomes. Understanding correlates of expressed emotion by family members of individuals with opioid use disorder is important, as this group faces high levels of stress and can play an important role in their loved ones' treatment. Thus, immediate family members of individuals who sought treatment for opioid problems ( N = 195) completed a web-based survey that included measures of expressed emotion, self-stigma, social support, and demographic characteristics. Multiple linear regression analyses were conducted to examine correlates of two types of expressed emotion—criticism and emotional overinvolvement. Results indicated that higher self-stigma and lower social support were significantly associated with higher emotional overinvolvement. Higher self-stigma and having experienced debt related to a family member's opioid use were associated with higher criticism. Thus, self-stigma and financial burden may exacerbate likelihood of expressed emotion, whereas social support may buffer against expressed emotion.